The Routledge companion to the sound of space - Matthews, Emma-Kate ca. 20./21. Jh; Burry, Jane 1957-; Burry, Mark 1957- (Routledge, Taylor & Francis Group, 2025)
"This Companion explores a range of conceptual and practical relationships between sound and space across various disciplines, providing insights from technical, creative, cultural, political, philosophical, psychological, and physiological perspectives. The content spans a wide range of spatial typologies, from large reverberant buildings to modest and intimate ones; from external public squares to domestic interiors; from naturally formed environments to highly engineered spaces. These compiled insights and observations explore the vast diversity of ways in which sonic and spatial realms interact. This publication therefore forms important bridges between the intricate and diverse topics of technology, philosophy, composition, performance, and spatial design, to contemplate the potential of sound and space as tools for creative expression and communication, as well as for technical innovation. It is hoped that by sharing these insights, the book will inspire practitioners, scholars, and enthusiasts to incorporate new perspectives and methodologies into their own work. Through a rich blend of theory, practice, and critical reflection, this volume serves as a valuable resource for anyone interested in exploring the intricacy of relationships between space and sound, whether they are students, professionals, or simply curious. Our companion provides a cross-section through shared territories between sonic and spatial disciplines from architecture, engineering, sound design, music composition and performance, urban design, product design and much more"--
Keywords: Raum; Klang; Sound / Social aspects